Exploring Students’ Self-Confidence in Speaking English Through Project-Based Learning - Bilal, M. Ahmad; Zul Astri; Nuraeni; Wahyuningsih; Masita, Syarifah; Wahab, Isnaeni; Aisyah, Sitti (Yayasan Cendekiawan Indonesia Timur, 2025)
The ability to communicate in English is very important in the era of globalization. However, many students face difficulties communicating in the language due to a lack of confidence. Self-confidence greatly affects students' speaking abilities. Studies show that confident students are more active and speak more often. Students lack confidence because traditional education methods are too theory-centered. Project-Based Learning (PBL) enhances students' confidence, critical thinking, and speaking skills by involving them in group projects.This research was conducted on 19 students at MA Bustanul Ulum. Through observation and interviews, it was found that PBL increases students' confidence in speaking English. Although there are challenges, such as shyness and group conflicts, these can be overcome with the help of the teacher. This research proves that PBL is effective in improving students' speaking skills.